Sanitation and safety in food vending machines in a public university: a preliminary study of standards and practices - Majid, Ain Fatini; Ab Mulup, Nor Amalina; Mohammed, Farhanna; Baharuddin, Azan Azuwan; Misebah, Fatimah Azzahra'; Abdul Halim-Lim, Sarina (RSIS International, 2024)
The demand for vending machines has significantly increased in a current modern lifestyle with a tight schedule and limited time. However, there is a critical concern to guarantee buyers about the safety of foods and drinks sold in vending machines. Therefore, this research aimed to identify the level of quality and safety parameters of food and drink products sold in the vending machines with the application on mixed methodology. For the quantitative data, structured observations were conducted on 15 food-handlers of the vending machine located in a tertiary educational institution in Selangor, Malaysia. The key results showed that the awareness of food handlers regarding the safety and quality of vending machines in the institution is poor due to the lack of training in food safety and hygiene. Currently, the food handlers are usually based on their experience, logic and common sense because they did not have any Standard Operation Procedure (SOP) towards the vending machine. The critical criteria for vending machines, safety and quality are the cleanliness of the machine and the surroundings, the equipment used, the products, the replenishing staff, the vehicles and transportation and the location of the machine. This study shed light by providing information about food safety and quality of food handlers towards the vending machine. The study has provided information on practice and the knowledge of the food handlers and increases awareness of the critical practice required to be implemented. This study able to critically improve the current assessment form used by the government and offer a self-assessment tool for industry in order to develop a strategic plan for their food quality and safety program.